Cross-Reaction Antibody Test between SARS-CoV-2 and Dengue Hemorrhagic Fever in Indonesia - Danny Luhulima; Tri Soetowo; Ria Amelia (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Coronaviruses are a family of viruses that cause illness from the common cold to severe diseases such as Severe AcuteRespiratory Syndrome (SARS-CoV). In December 2019, forty new cases of pneumonia of unknown etiology have beenreported in Wuhan, China. The disease resembles Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV) and hasbeen subsequently named the 2019-novel Coronavirus Disease (COVID-19). The antibody test is a blood test that providesquantitative and qualitative detection of IgG and IgM antibodies against the SARS-CoV-2. Reported a male, 43-year oldsuffering from DHF, but the results of an IgG and IgM rapid test were COVID-19 reactive. Also, reviewed rapid tests forCOVID-19 and the results showed that only IgG was reactive. This explained that the patient already had SARS Cov-2antibodies but was not suffering from the disease. The rapid test COVID-19 IgM result was deemed to be a false positive.